Validity and Reliability of the Indonesian Version of General Self-Efficacy Scale (GSES) with Disasters - Lidya, Herlin; Noviana, Uki; Haryani, Haryani; Alim, Syahirul; Setiyarini, Sri (Journal of Language and Health, 2024)
Disasters preparedness behavior is influenced by self-efficacy. Self-efficacy affects the resilience and ability of communities in adapting to changes in disaster conditions. In Indonesia there are no instruments for measuring self-efficacy in the context of disasters. Objective: This study aimed to adapt the Indonesian version of the General Self-Efficacy Scale into the context of disasters and test its validity and reliability. The Indonesian version of General Self-Efficacy Scale was adapted culturally then modified into the disaster context and adapted to the research target culture and also tests of the content validity and the construct validity were conducted on 100 residents. The analysis used Pearson product-moment, exploratory factor analysis and confirmatory factor analysis. Reliability testing used internal consistency analysis (Cronbach’s alpha). The Indonesian version of the General Self-Efficacy Scale was in accordance with the context of the disaster and the target culture of the study. Pearson correlation values ​​range from 0.528 to 0.707. The EFA results were formed of 2 factors. Confirmatory factor analysis with 2 factors showed a fit model (p-value = 0.032, SRMR = 0.078, CFI = 0.91). The CFA results with 1 factor showed a fit and very good model (p-value = 0.135, RMSEA = 0.058, SRMR = 0.060, CFI = 0.977). The Cronbach’s alpha coefficient has a value of 0.847. The Indonesian version of the General Self-Efficacy Scale in the context of disaster with a 2-factor model and a 1-factor model shows acceptable validity and reliability for measuring self-efficacy in the face of disasters.